Minimally invasive cartilage myringoplasty: our technique and experience - Ballal, Venkatesh C.; Shivappa, Lohith; Tmmappaiah, Subramanya B.; Basavannaiah, Sphoorthi; Rangaswamy, Chandralekha T. V. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic suppurative otitis media is an inflammatory process in the middle ear and is an important health problem in India. Myringoplasty is the most common procedure performed that aims to close the tympanic membrane perforation which is traditionally done with temporalis fascia graft under microscope. Recent studies using the transcanal cartilage “push-through” technique of myringoplasty have demonstrated that it to be very feasible and effective. The aims and objectives of the study was to analyze the results of endoscopic transcanal ‘push-through’ myringoplasty in dry small central perforations in cases of inactive mucosal type of chronic ottitis media. Methods: This retrospective study was conducted in 16 patients who underwent transcanal endoscopic cartilage ‘push through’ myringoplasty and patients were called for regular follow up for 12 weeks and results were statistically analysed. Results: A total of 16 cases were included in the present study. The graft uptake rate in the present study was found to be 93.75%. The mean preoperative air bone gap was 21.76 dB and the mean postoperative air bone gap was reduced to 12.6 dB. The air bone gap was 10 dB or less in 37.5% ears. Conclusions: Endoscopic push-through technique of cartilage myringoplasty is an effective, minimally invasive and feasible method and has good success rate in terms of graft uptake as well as hearing gain. It may also represent a first choice approach for small and medium sized tympanic membrane perforations.